Regulation of apoptosis by viral gene products - Teodoro, J G; Branton, P E (Journal of virology, 1997)
Apoptosis is the process whereby individual cells of multicellular organisms undergo systematic self-destruction in response to a wide variety of stimuli. Apoptosis is a genetically controlled preprogrammed event which eliminates cells during development when they have become redundant or which functions as an emergency response after radiation damage, viral infection, or aberrant growth induced by the activation of oncogenes. The purpose of this review is to summarize recent information on the induction and suppression of apoptosis by viral products as well as to propose how this knowledge may provide insights into basic cell biology and offer the potential of new therapeutic applications. A recent comprehensive review by Shen and Shenk (75) also deals with some aspects of the subjects covered below.